Continuous synthesis of menthol from citronellal and citral over Ni-beta-zeolite-sepiolite composite catalyst - Simakova Irina; Mäki-Arvela Päivi; Martinez-Klimov Mark; Muller Joseph; Vajglova Zuzana; Peurla Markus; Eränen Kari; Murzin Dimitry Yu. (Elsevier B.V., 2022)
One-pot continuous synthesis of menthols both from citronellal and citral was investigated over 5 wt% Ni supported on H-Beta-38-sepiolite composite catalyst at 60–70 °C under 10–29 bar hydrogen pressure. A relatively high menthols yield of 53% and 49% and stereoselectivity to menthol of 71–76% and 72–74% were obtained from citronellal and citral respectively at the contact time 4.2 min, 70 °C and 20 bar. Citral conversion noticeably decreased with time-on-stream under 10 and 15 bar of hydrogen pressure accompanied by accumulation of citronellal, the primary hydrogenation product of citral, practically not affecting selectivity to menthol. A substantial amount of defuctionalization products observed during citral conversion, especially at the beginning of the reaction (ca. 1 h), indicated that all intermediates could contribute to formation of menthanes. Ni/H-Beta-38-sepiolite composite material prepared by extrusion was characterized by TEM, SEM, XPS, XRD, ICP-OES, N2 physisorption and FTIR techniques to